PEMBERIAN PEMBEBASAN BERSYARAT KEPADA NARAPIDANA DIKAITKAN DENGAN UNDANG-UNDANG PEMASYARAKATAN - Flora, Henny Saida (Universitas Medan Area, 2014)
Parole is a form of training for inmates in prisons are given to those who haveundergone the punishment is two- thirds of the sentence , or at least ninemonths have been undertaken. Must undergo criminal inmates for good behavioras well as meet other requirements that have been set for it . During his paroleinmates given probation in which there is general agreement and relatedagreements . The purpose of the probationary period is to provide theopportunity for inmates granted parole to improve their behavior and realize themistakes he had made. Thus inmates to adjust himself to the life of societywhich in turn is expected to be a good citizen , useful and responsible beforeending its criminal past .